PEMANFAATAN SASTRA ANAK SEBAGAI MEDIA PENUMBUHAN BUDI PEKERTI - Siti Anafiah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Abstract: The existence of a literary work is very important for children. Children's literature is an imaginative work of art with aesthetic elements that dominant language medium, both oral and written, which in particular can be understood by children and contains the world are familiar with the children. Through reading literature, children can explore many benefits. Children's literature has an important contribution in the effort put forth generation of intelligent and moral as expected. Literature is believed to assist in the growth of children's character, because in the literary works contained positive values, since the values of the cultural, social, moral, humanitarian, to religion. Therefore, it becomes important, literature taught in schools. That way, the child is not only smart intellectually, but also emotionally intelligent, spiritual, and social.